Документи про життя і діяльність академіка М.Ф. Кащенка у музеї історії Національного ботанічного саду ім. М.М. Гришка НАН України - Chuvikina, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The documents described in the paper are dedicated to life and work of Mykola Feofanovych Kaschenko, who was Academician, one of the first founders of the Ukrainian Academy of Sciences. These documents are exhibited in the Museum of History of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine.